Adaptive Control System of an Electromagnetic Actuator for the Quickly Moving Flap of an Air-impulse-charging Internal Combustion Engine without using Position, velocity, or Acceleration Sensors. (2015) - Pavlenko, A.V.; Gummel, A.A.; Bolshenko, I.A.
Abstract: An adaptive control algorithm of a fast electromagnetic actuator has been developed without using position, velocity, or acceleration sensors. The algorithm is based on the fluctuation rate of the current in the electromagnet coil, which is measured during anchor movement. The proposed method and control algorithm compensate for external mechanical factors and are based on the interconnection of electric processes in the electromagnetic actuator coil, with mechanical processes relating to the movement of the movable element of the magnetic system. A structural diagram of a hardware device and an algorithm that implement the proposed control method are presented for a resonance type electromagnetic actuator, where there is a current change in the coil of the electromagnetic actuator. At each switching of the drive, parameters are controlled, and the length of pulse-width-modulated pulses is adjusted to ensure reliable switching and regulation of the anchor end. The control system responds to the disturbance in the current switching cycle. To test the adequacy of the proposed algorithm, an experimental model of an actuator with the proposed control system has been constructed, and its characteristics have been studied. It has been found out that the proposed algorithm ensures the required performance in terms of the operation speed and the lowest speed of the anchor landing without using position, velocity or acceleration sensors under external mechanical effects.